Development and Evaluation of Mathventur: An Android-Based Mobile Educational Game to Enhance Elementary Students Learning Motivation and Mathematics Achievement - Trisnawati Trisnawati; Lailatun Nisa; Lilis Tri Handayani (YHMM PUBLISHING, 2026)
This study aims to develop an Android-based educational game application called Mathventur, designed to increase elementary students’ interest in learning mathematics at SDN 1 Wates Selatan. The research was motivated by students’ low interest in math, often seen as difficult and boring. The development process followed the Waterfall method, including needs analysis, system design using UML, implementation via Thunkable, and testing through blackbox testing. Data collection methods included observation, interviews, and literature review. The testing results showed that all features functioned correctly according to design. A trial involving 10 students indicated 90% positive responses, particularly in ease of use and visual appeal. Teacher assessments resulted in an average score of 88%, confirming the application’s feasibility as a learning tool. The quiz feature, automatic scoring, and interactive visual materials for topics like addition and division effectively improved students’ engagement and understanding. In conclusion, Mathventur serves as an innovative and enjoyable teaching medium that successfully encourages students to learn independently and with greater enthusiasm.